2023
DOI: 10.3233/jad-230106
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Database Analysis of Risk Factors Associated with Decreased Activities of Daily Living in Patients with Alzheimer’s Disease

Abstract: Background: Preserving activities of daily living (ADL) is the key issue for Alzheimer’s disease (AD) patients and their caregivers. Objective: To clarify the ADL level of AD patients at diagnosis and the risk factors associated with decreased ADL during long-term care (≤3 years). Methods: Medical records of AD patients in a Japanese health insurance claims database were analyzed retrospectively to determine ADL using the Barthel Index (BI) and identify the risk factors associated with decreased ADL. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…One study involving nightshift workers in the United States found that individuals with a shorter sleep duration (<7 hours/day) had the highest prevalence of sleep problems (61.8%) and the highest prevalence of an impaired ADL score (24.8%) [ 48 ], revealing a correlation between shorter sleep duration and higher risk of ADL disability. Another study focusing on patients with dementia discovered that a longer sleep duration was associated with ADL disability [ 49 ]. Similarly, a cross-sectional study that recruited 1798 participants older than 90 years found that a long sleep duration (≥12 hours) may be associated with an increased risk of ADL disability for this population [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study involving nightshift workers in the United States found that individuals with a shorter sleep duration (<7 hours/day) had the highest prevalence of sleep problems (61.8%) and the highest prevalence of an impaired ADL score (24.8%) [ 48 ], revealing a correlation between shorter sleep duration and higher risk of ADL disability. Another study focusing on patients with dementia discovered that a longer sleep duration was associated with ADL disability [ 49 ]. Similarly, a cross-sectional study that recruited 1798 participants older than 90 years found that a long sleep duration (≥12 hours) may be associated with an increased risk of ADL disability for this population [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study involved night shift workers in the United States found that the prevalence of shorter sleep duration (< 7 hours/day) was the highest sleep problems among night shift workers (61.8%) with the highest prevalence of impaired ADL score (24.8%) 47 , which revealed a correlation between shoter sleep duration and higher risk of ADL disability. Another study focused on dementia patients discovered that longer sleep duration was associated with ADL disability 48 .…”
Section: Comparison With Prior Workmentioning
confidence: 99%